The Makkatte’ Tradition in The Bugis Muslim Community: A Gender and Cultural Analysis - Nabiela Naily; Rustriningsih (IBDA` : Jurnal Kajian Islam dan Budaya, 2025)
Female circumcision in the Bugis Muslim community is one of the processions in affirming one's Islamic faith. What makes female circumcision problematic is the gender, health and cultural issues involved. Religious interpretations of the legal status of female circumcision, traditions and the impact or health risks of the practice have many aspects to analyze in more depth. Therefore, this paper aims to show how the tradition of the practice of makkatte’ (female circumcision) has developed in the Bugis Muslim community in South Sulawesi and is examined using gender analysis. This paper shows that there are differences in the practice of makkatte’ tradition in the Bugis Muslim community. In addition, this paper also shows that the makkatte’ tradition is influenced by religious factors under the pretext of being a form of consecration of religious perfection and on the other hand, tradition factors as a form of cultural conservation. From a gender perspective, the practice of makkatte’ in Bugis society is found to have improved gender conditions. Despite experiencing an increase in gender conditions which in practice is not dangerous, the practice of makkatte’ can be risky for girls' psychology because it continues to infringe on women's privacy.